Applied developmental psychology : theory, practice, and research from Japan - Shwalb, David W.; Nakazawa, Jun; Shwalb, Barbara J. (Emerald Publishing Limited : Information Age Publishing, 2005)
This volume provides an overview of recent research on child development in Japan. Sixteen contributions from leading psychologists cover such topics as the development of manga (comic book) literacy, the study of mathematics in school, and the effects of job- related temporary father absence.
Keywords: Child psychology -- Japan.; Psychology -- Developmental -- Child.; Child, developmental and lifespan psychology.; Age groups: children.; elektronické knihy; electronic books